The Orthodox Issue in Jordan: The Struggle for an Arab and Orthodox Identity. (December 2018) - Hager, Anna
Abstract : Scholarship on Christians in the Middle East has paid little attention to the role the Christian laity has played in defining and maintaining Christian identity and community boundaries. The so-called Orthodox issue ( al-qaḍya al-urthudhuksiyya in Arabic) enhances our understanding of this role. It is an ongoing conflict within the Greek Orthodox Patriarchate of Jerusalem between the church leadership of Greek extraction and the Arab – usually lower-ranking – clergy and laity. This article uses a case-study approach to a series of protests in Jordan in 2014 against a decision by the Patriarchate to relocate a local reform-minded cleric. Using ethnographic, historical and philological methods, I argue that through their engagement in this struggle, Greek Orthodox Jordanians assert their identity as Christians, as Arabs and as loyal Jordanians. This offers a perspective into the complex interplay between church—community relations, the issue of pastoral care, and this community's identity.